Balance of glutathione system activity in ascitic ovarian tumor under the experimental conditions - Sarakhan, V. (Journal of Education, Health and Sport, 2024)
The article presents the experimental results of the investigation the glutathione system activity in rats simulated ovarian ascites tumor. It was found that the glutathione system in the form of glutathione reductase and glutathione peroxidase is inactivated after 2 months, but at 4 months of study the activity of these enzymatic systems increases. Treatment with gammaglobulins gives a certain therapeutic effect due to a change in the activity of the studied enzymes involved in redox intracellular reactions. It was established that for 2 months activation of glutathione peroxidase with parallel inhibition of glutathione reductase. However, for 4 months the activity changed in the opposite direction.